Drugs and dietary supplements: what can we prescribe to patient and when - Oksana D. Nemyatyh; Sergey K. Zyryanov; Anatoliy V. Abricov (LLC "MEDIAFORMAT", 2023)
Probiotic drugs are currently widely used in clinical practice. However, the items offered in the today's Russian pharma market may have a registration status of dietary supplements (BAAs) that is fundamentally different in approaches to development. BAAs are not drugs, their production and selling is not subject to licensing. Experts of pharma market and healthcare system together with the legal professional address difficulties related to BAA prescription in clinical practice. In contrast to drugs, BAAs have no indications for use registered and confirmed by the regulatory authority, while each indication stated in the instructions for medical use of the drug is based on the results of appropriate studies. In this regard, it is extremely important to ensure that patients understand the real BAA effects and clearly state that it is not a drug, since, in case of damage caused to the life and health of the patient, medical institution and the physician shall bear civil liability.